Age alters cardiac autonomic modulations during and following exercise-induced heat stress in females. Issue 2 (3rd April 2018) - Leicht, Anthony S.; Flouris, Andreas D.; Kaltsatou, Antonia; Seely, Andrew J.; Herry, Christophe L.; Wright Beatty, Heather E.; Kenny, Glen P.
ABSTRACT: The aim of this study was to examine the effect of natural ageing on heart rate variability during and following exercise-induced heat stress in females. Eleven young (∼24 years) and 13 older (∼51 years), habitually active females completed an experimental session consisting of baseline rest, moderate intensity intermittent exercise (four 15-min bouts separated by 15-min recovery) and 1-hour of final recovery in a hot and dry (35°C, 20% relative humidity) environment. Respiratory and heart rate recordings were continuously logged with 10-min periods analysed at the end of: baseline rest; each of the exercise and recovery bouts; and during the 1-hour final recovery period. Comparisons over time during exercise and recovery, and between groups were conducted via two-way repeated-measures ANCOVAs with rest values as the covariate. During baseline rest, older females exhibited lower heart rate variability compared to young females with similar levels of respiration and most (∼71-79%) heart rate variability measures during repeated exercise and recovery. However, older females exhibited heart rate variability metrics suggestive of greater parasympathetic modulation (greater long axis of Poincare plot, cardiac vagal index; lower low-high frequency ratio) during repeated exercise with lower indices during the latter stage of prolonged recovery (less very low frequency component, Largest Lyapunov Exponent; greater cardiac sympathetic index). The current study documented several unique, age-dependent differences in heart rate variability, independent of respiration, during and following exercise-induced heat stress for females that may assist in the detection of normal heat-induced adaptations as well as individuals vulnerable to heat stress.